(untitled) (Bodhi Path, 2023)
The ancient guru-based education system is familiar to us all. The Buddhist universities were also based on this system. While the Buddhist universities were more extensive and vast than the guru-based system, students from wealthy and upper-class society tended to attend guru-based schools, while the Buddhist universities were open to all. These universities were known for their education and knowledge. The kings of the era contributed significantly to their construction and preservation. Although the contributions of the kings were spiritual in nature, they were funded by their treasury. During the Pala Dynasty, the main Buddhist universities were Nalanda, Vikramaśila, Odantapuri, Jagaddala and Somapura in Bengal. Not only Buddhist literature, but also various branches of knowledge such as logic, grammar, medicine, and fine arts were taught in these universities.